Matemática financeira: uma proposta para o ensino médio - Estevam, Luís Felipe Christofoletti [UNESP] (2015)
The main goal of this work was to explore thoroughly the basic financial math. In this perspective, we sought the relation between this content and others which configure the educational curriculum guidelines. We tried to reflect on the contextualization of the financial math in the high school, and to show different ways to teachers to explore this theory in class. For that purpose, we demonstrated some result in a different manner and presented some exercises